Official development assistance, social capital and growth in Latin America - Neira, Isabel (2016)
This study focuses on the relationship among official development assistance (ODA), social capital and economic growth in Latin American countries, attempting to determine whether the impact of such assistance on growth is conditional on the receiving country’s stock of social capital. To this end, we use “trust” to measure social capital in an unbalanced panel of 18 Latin American countries over the period 2001-2010. After accounting for country and time effects in a dynamic panel data model, our results show that the impact of ODA on growth is indeed conditional on the level of trust that exists. This suggests that this assistance will be more effective when used in a trust-rich environment.